Understanding Australian healthcare workers' uptake of influenza vaccination: examination of public hospital policies and procedures - Seale Holly; Kaur Rajneesh; MacIntyre C (BMC, 2012)
Abstract Background In Australia, whether to provide free influenza vaccine to health care workers (HCWs) is a policy decision for each hospital or jurisdiction, and is therefore not uniform across the country. This study explored hospital policies and practices regarding occupational influenza vaccination of HCWs in Australia. Methods A study using qualitative methodology, which included semi-structured interviews, was undertaken with hospital staff involved with the delivery of occupational influenza vaccination from three states in Australia. Results The 29 participants were responsible for vaccinating staff in 82 hospitals. Major themes in the responses were the lack of resources and the difficulties participants faced in procuring any additional support or funding from their institutions. All study sites provided vaccine free of charge to employees via on-site clinics or mobile carts, and used multiple strategies to inform and educate their staff. In some instances, declination forms had been adopted, however their use was associated with resourcing issues, animosity, and other problems. Participants who were responsible for multiple sites were more likely to recount lower vaccination coverage figures at their hospitals. Conclusions From these interviews, it is clear that hospitals are implementing multiple strategies to educate, promote, and deliver the vaccine to staff. However, resources and support are not always available to assist with the vaccination campaign. The reality for many hospitals is that there is limited capacity to implement the vaccination campaigns at the levels high enough to raise compliance rates. Further research needs to be conducted to quantify the factors contributing to higher uptake in the Australian hospital setting.